An Experiential Approach to Psychopathology 2016
DOI: 10.1007/978-3-319-29945-7_3
|View full text |Cite
|
Sign up to set email alerts
|

The Window and the Wound: Dysphoria and Anger in Borderline Disorders

Abstract: Carla is a twenty-five-years-old young woman with pensive and penetrating eyes. She looks dynamic and intelligent. She has come to see me unwillingly, pushed by her mother. Their relationship, she tells me, is (and always has been)a very conflictual one. Her mother "accuses" her of being constantly distracted, careless and inefficient both in life and at work; she also reproaches her for being extremely oppositional and for making life impossible for everyone in the family with her constant outbursts. Carla, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Sometimes, this identification with others metamorphoses into dilution or diffusion of the self. Then the person adopts the form and characteristics of their casual partner and loses themselves in it [44]. These experiences are accentuated during periods of stress in which individuals with BPD can experience dissociative symptoms, such as losing a sense of themselves (depersonalization) or their environment (derealization).…”
Section: Discussion: Reconfiguration Bpd’s Experiences Of Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, this identification with others metamorphoses into dilution or diffusion of the self. Then the person adopts the form and characteristics of their casual partner and loses themselves in it [44]. These experiences are accentuated during periods of stress in which individuals with BPD can experience dissociative symptoms, such as losing a sense of themselves (depersonalization) or their environment (derealization).…”
Section: Discussion: Reconfiguration Bpd’s Experiences Of Selfmentioning
confidence: 99%
“…Perhaps one of the most common experiences reported by people with BPD is a sense of emptiness . This emptiness, which has nothing to do with a form of freedom or casualness, is experienced as a weight that pulls the self down [44] and takes on several determinations [45]: the sense of emptiness is lived as a feeling of internal absence [4], an impression of deadness, nothingness, a void feeling swallowed [46], a sense of vagueness [47], an internal hole or vacuum, aloneness [48], an impression of woodenness [49], and numbness and alienation [10]. In the narrative interpretation of TPL, this feeling has been related to the absence of a stable and coherent history of self and thus to a breakdown in what we have termed the self-institution.…”
Section: Discussion: Reconfiguration Bpd’s Experiences Of Selfmentioning
confidence: 99%
“…Although this question arguably has implications for forensic matters pertaining to assessments of culpability, e.g., where BPD impulsivity leads to criminal actions, I am primarily concerned with the implications this question has for a psychotherapeutic context. It has often been shown that selfdirected emotions, such as guilt and shame in particular, play vital roles in BPD, and that the characteristic anger present in BPD may be understood as resulting from these emotions [48,49,50,30]. In light of the above sketched framework, such emotions may be understood as (at least partially) resulting from experiences of being confronted with affects and responses that properly belong to oneself, but which are not growing out of a reflectively shaped intention.…”
Section: Personal Responsibility Between Alienness and Narrative Self...mentioning
confidence: 99%